Cricetus cricetus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
18. Common Hamster Cricetus cricetus French: Hamster d'Europe / German: Feldhamster / Spanish: Hamster comun Other common names: Black-bellied Hamster, European Hamster, German Marmot (archaic), Great Hamster Taxonomy. Mus cricetus Linnaeus, 1758, «“ Habitat.. in Germania. [= Germany]. ”» Nine subspecies of C. cricetus were recognized in the past, but that number grossly exaggerated and obscured actual patterns of geographic variation. Phylogeographical architecture is largely the outcome of the Last Glacial Maximum, and estimated times of divergence among phylogroups vary between 10,000 and 150,000 years. Greatest genetic and morphological diversity occurs in the western segment of the distribution. Populations occurring east of the Carpathian Mountains are rather uniform, containing a single phylogeographical line. There is no agreement over the recognition of subspecies. Monotypic. Distribution. From W Europe E to the River Yenisei in Siberia, including Belgium, Netherlands, France, Germany, Poland, Czech ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 286-288, DOI: 10.5281/zenodo.6707142 ...